2017
DOI: 10.1155/2017/4151738
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Evaluation of the Parkinson’s Disease Activities of Daily Living Scale

Abstract: Objective To evaluate a set of psychometric properties (i.e., data completeness, targeting, and external construct validity) of the Parkinson's disease Activities of Daily Living Scale (PADLS) in people with Parkinson's disease (PD). Specific attention was paid to the association between PADLS and PD severity, according to the Hoehn & Yahr (H&Y) staging. Methods The sample included 251 persons with PD (mean age 70 [SD 9] years). Data collection comprised a self-administered postal survey, structured interviews… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
0
6
0
1
Order By: Relevance
“…In previous studies, HCQ showed comparable satisfactory internal consistency of the subscales in 66-69 and 65-91 year olds, and good testretest reliability in 65-91 year olds in Germany [30]; internal consistency in the HHPD baseline sample was acceptable [31]. For the current study, the total score combining two scales was dichotomised at 50% cut-off into low [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] and high (34-80) external HCB. GSE was assessed by the self-administered 10-item General self-efficacy Scale [32] at T1.…”
Section: Moderators: External Hcb and Gse At T1mentioning
confidence: 77%
See 3 more Smart Citations
“…In previous studies, HCQ showed comparable satisfactory internal consistency of the subscales in 66-69 and 65-91 year olds, and good testretest reliability in 65-91 year olds in Germany [30]; internal consistency in the HHPD baseline sample was acceptable [31]. For the current study, the total score combining two scales was dichotomised at 50% cut-off into low [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] and high (34-80) external HCB. GSE was assessed by the self-administered 10-item General self-efficacy Scale [32] at T1.…”
Section: Moderators: External Hcb and Gse At T1mentioning
confidence: 77%
“…The respondents were asked to tick the one of five descriptions, which best described how Parkinson's disease had affected their day-to-day activities in the last month (scores 1-5, higher = more difficulty/dependence). PADLS is a reliable and valid measure of ADL in people with PD [25,26]. For this study, PADLS scores were dichotomised into no/mild difficulties (original scores 0-1 = score 0) or moderate/ severe/extreme difficulties (original scores 3-5 = score 1), which is a principle used in previous studies [26,27].…”
Section: Primary Outcome: Generic Adl At T2mentioning
confidence: 99%
See 2 more Smart Citations
“…), comorbidities, and perceived general health according to item 1 of the RAND-36 questionnaire ("poor" through "excellent," scored 0-4) [56,57]. PwPD also rated their difficulties in daily life using the PD Activities of Daily Living Scale (PADLS; "no difficulties" through to "extreme difficulties," scored 1-5) [58,59], perceived burden due to PD ("none at all" through to "extreme," scored 0-4), frequency of memory problems according to item 32 of the PDQ-39 ("never" through to "always," scored 0-4) [60,61], and provided information on the presence or absence of motor fluctuations and dyskinesias, time since diagnosis, number of daily medication intakes, and current medical PD therapy.…”
Section: Interventionmentioning
confidence: 99%